Overcoming treatment resistance in cancer: Current understanding and tactics. (28th February 2017) - Wu, Guang; Wilson, George; George, Jacob; Liddle, Christopher; Hebbard, Lionel; Qiao, Liang
Highlights: Considering many tumor recurrences after chemotherapy, treatment resistance has attracted great scientific attention. There have been some seminal discoveries, such as sequential mutations and cancer stem cells. The successful treatment of cancer still requires a considerable refinement of our knowledge concerning treatment resistance. We expect that a more informed and refined approach to treat cancer will be developed and this may improve prognosis of cancer patients. Knowledge about the failure of cancer treatments and potential approaches to overcome therapeutic resistance is discussed. Abstract: Chemotherapy is the standard treatment for many, if not all, metastatic cancers. While chemotherapy is often capable of inducing cell death in tumors leading to shrinkage of the tumor bulk, many patients suffer from recurrence and ultimately death due to resistance. During the last decade, treatment resistance has attracted great attention followed by some seminal discoveries, including sequential mutations, cancer stem cells, and bidirectional inter-conversion of stem and non-stem cancer cell populations. Nevertheless, the successful treatment of cancer will require a considerable refinement of our knowledge concerning treatment resistance. In doing so, we expect that a more informed and refined approach to treat cancer will be developed and this may improve prognosis of cancer patients. In this review, we will discuss the current knowledge concerning the failure of cancer treatments and the potential approaches to overcome therapeutic resistance.